Pengaruh Islamic Attributes, Destination Image, dan Accessibility Terhadap Kepuasan WIsatawan di Lego-Lego Centre Point of Indonesia Makassar: The Influence Islamic Attributes, Destination Image, and Accessibility on Tourist Satisfaction at Lego-Lego Centre Point of Indonesia Makassar - Nur Ahmad Ihsan; A. Syathir Sofyan; Muhammad Nasri Katman (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2024)
This study aims to analyze the influence of Islamic attributes, destination image and accessibility on tourist satisfaction at the lego-lego centre point of Indonesia Makassar. The data used is sourced from a questionnaire in the form of a google form link (primary data). The sampling method uses the purposive sampling method , which is a sample determination technique based on certain criteria or considerations. The results of the study show that Islamic attributes, destination image and accessibility have a positive and partially significant effect on tourist satisfaction at the lego-lego centre point of Indonesia Makassar. As long as the high Islamic attributes, destination image and accessibility will increase tourist satisfaction at the lego-lego centre point of Indonesia Makassar. This study uses a quantitative method, the population of this study is lego-lego center point of Indonesia Makassar tourists. The instruments used were questionnaires and data analysis techniques using multiple regression. The results of the coefficient test of Islamic attributes, destination image and accessibility regression showed an influence on tourist satisfaction. Meanwhile, the results of the t-test that islamic attributes, destination image and accessibility showed that they had a positive and partially significant effect on tourist satisfaction at the lego-lego centre point of Indonesia Makassar.